Understanding the Lymph Node Microenvironment in Metastatic and Non-Metastatic Head and Neck Squamous Cell Carcinoma: A Systematic Review - Antoine Yanni; Géraldine Descamps; Fabrice Journe; Edward Boutremans; Isabelle Loeb; Sven Saussez; Didier Dequanter (Journal of Personalized Medicine, 2026)
Background: The immune landscape in head and neck squamous cell carcinoma (HNSCC) has been widely investigated. However, the crucial role played by the lymph node microenvironment in metastatic and non-metastatic HNSCC remains unknown. This systematic review aims to discuss the immunological crosstalk between the tumor and the nodal microenvironment and to describe the distribution of immune cells in metastatic and non-metastatic lymph nodes. Methods: A systematic review was conducted according to the PRISMA guidelines. PubMed, Scopus, and the Cochrane Library were searched for studies published between 1990 and 2025, with the final search performed in December 2025. Prospective and retrospective studies evaluating immune cell infiltration in metastatic and non-metastatic cervical lymph nodes were included, whereas studies focusing exclusively on non-cellular biomarkers and non-English publications were excluded. The risk of bias was assessed using the Newcastle–Ottawa Scale. The results were synthesized narratively, and no meta-analysis was performed. Results: The screening process identified 608 articles, of which 27 met our predefined inclusion criteria. These studies focused on macrophages, dendritic cells, neutrophils, natural killer cells, T helper cells, cytotoxic T cells, regulatory T cells, B cells, total lymphocytes, and surface markers. This systematic review provides a well-structured analysis of current knowledge on the impact of the innate and adaptive immune systems on the response against cancer cells and the recruitment of immune cells in lymph nodes. The most significant findings highlight the crucial role of antigen presentation in the antitumor response, particularly through the recruitment and activation of dendritic cells and subcapsular sinus macrophages in tumor-draining lymph nodes. It also presents in a fairly comprehensible manner that the density of mature dendritic cells, cytotoxic T cells, and B cells is higher in non-metastatic lymph nodes. Discussion: The lymph node microenvironment is highly enriched with immune cell infiltration, and their distribution between metastatic and non-metastatic lymph nodes can contribute to a better understanding of the underlying pathological processes. Particular attention should be given to the innate immune system cells and their implication in antigen presentation. Our findings suggest that identifying immunological profiles of lymph nodes may provide a rationale for treatment de-escalation protocols and raise the question of lymph node preservation in antitumor immune responses. However, the heterogeneity and bias assessment of the included studies warrant a cautious interpretation of these findings. Another important limitation is the limited number of studies comparing the immune microenvironment of primary tumors and lymph nodes.